THE MYTH OF HOMECOMING in THE FILM PURANG BY AZHAR KINOI LUBIS A STUDY OF ROLAND BARTHES' SEMOTICS - Mufti Isror Alfarobby; Ririe Rengganis (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
ABSTRACT The film that will be studied in this research is